Biological inorganic chemistry : a new introduction to molecular structure and function - Crichton, Robert R. (Amsterdam, Netherlands ; Oxford, UK ; Boston [Mass.] : Elsevier, 2012)
The importance of metals in biology, the environment and medicine has become increasingly evident over the last twenty five years. The study of the multiple roles of metal ions in biological systems, the rapidly expanding interface between inorganic chemistry and biology constitutes the subject called Biological Inorganic Chemistry. This revised and expanded text, written by a biochemist, with a long career experience in the field (particularly iron and copper) presents an introduction to this exciting and dynamic field. The book begins with introductory chapters, which together constitute an overview of the concepts, both chemical and biological, which are required to equip the reader for the detailed analysis which follows. Pathways of metal assimilation, storage and transport, as well as metal homeostasis are dealt with next. Thereafter, individual chapters discuss the roles of sodium and potassium, magnesium, calcium, zinc, iron, copper, nickel and cobalt, manganese, and finally molybdenum, vanadium, tungsten, chromium and selected non-metals. The final five chapters provide a tantalising view of the roles of metals in brain function, biomineralization and a brief illustration of their importance in both medicine and the environment. Relaxed and agreeable writing style. The reader will not only fiind the book easy to read, the fascinating anecdotes and footnotes will give him pegs to hang important ideas on. Written by a biochemist. Will enable the reader to more readily grasp the biological and clinical relevance of the subject. Many colour illustrations. Enables easier visualization of molecular mechanisms Written by a single author. Ensures homgeneity of style and effective cross referencing between chapters.
An overview of metals and selected nonmetals in biology -- Basic coordination chemistry for biologists -- Structural and molecular biology for chemists -- Biological ligands for metal ions -- An overview of intermediary metabolism and bioenergetics -- Methods to study metals in biological systems -- Metal assimilation pathways -- Transport, storage and homeostatis of metal ions -- Sodium and potassium : channels and pumps -- Magnesium : phosphate metabolism and photoreceptors -- Calcium : cellular signalling -- Zinc : Lewis acid and gene regulator -- Iron : essential for almost all life -- Copper : coping with dioxygen -- Nickel and cobalt : evolutionary relics -- Manganese : oxygen generation and detoxification -- Molybdenum, tungsten, vanadium and chromium -- Nonmetals in biology -- Biomineralisation -- Metals in brain -- Metals and neurodegeneration -- Metals in medicine and metals as drugs -- Metals in the environment.
Previous edition: 2008.
Includes bibliographical references and index.
Keywords: Bioinorganic chemistry; SCIENCE -- Life Sciences -- Biochemistry; Bioinorganic chemistry